Theme, Characterisation, Background, Plot, and Social Class in the Novels Gadis Pantai and Para Priyayi: An Intertextual Review - Fikr, Hasnul; ., Syofiani; Setiwati, Dilaila (KnE Social Sciences, 2022)
This study aimed to describe the intertextual relationship between the novel Gadis Pantai by Pramoedya Ananta Toer and the novel Para Priyayi by Umar Kayam through the analysis of theme, characterization, setting, plot, and social class. This was qualitative descriptive research. Based on the data analysis, it was found that there are differences in the intrinsic elements of both novels, namely: (a) the theme of the Gadis Pantai novel is humanity, while the theme of the Para Priyayi novel is the struggle for a better life; (b) the main characters in Gadis Pantai are Gadis Pantai and Bendoro, while the main characters in Para Priyayi are Sastrodarsono and Lantip; (c) Gadis Pantai uses a nineteenth-century setting (in Rembang Regency and the Javanese social background), while Para Priyayi uses a setting of 1910 (in Wanagalih, Wanalawas, Yogyakarta, Solo, and Jakarta, with a Javanese social background); and (d) Gadis Pantai uses a chronological plot, while Para Priyayi uses a mixed plot. Also, the social class of the characters in the two novels consist of the priyayi and the wong cilik class, but differences exist in the ways presented to obtain social status. We can conclude that the novel Gadis Pantai is a hypogram whereas the novel Para Priyayi is a transformation. Keywords: Gadis Pantai novel, Para Priyayi novel, social class, intertextual studies, Javanese culture